(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The digital era has made life easier and faster, but there is an opposing viewpoint that technology can be destructive to humans. Records Management (RM) and Electronic Records Management (ERM) are two activities that have been shown to be advantageous in the workplace. Record Management (RM) oversees the effective and systematic control of the creation, receipt, maintenance, use, and disposition of records, while ERM oversees the effective and systematic control of the creation, receipt, maintenance, use, and disposition of records. Records management is an essential task that enhances a company and can be part of its culture. E-Med Healthcare Solutions Incorporated is one of the companies focused on exceeding their client’s expectations by providing excellent products, outstanding customer support service, greater value, and increased flexibility. The accuracy of records showed that all information about each patient was true and precisely recorded in the system, while e-med Healthcare Solutions Inc. integrated record management as part of daily operations. The processing of data in the Medix information system demonstrated how well the system functions and the sending and receiving of data demonstrated how quickly and accurately the system offers accurate information and can handle large files. The system is office-friendly and secure against data loss, but the system software is not updated. The questionnaire was given to the employees and created effective and practical questionnaires with the help of grammarians and statisticians. The program offers a secure method of filing, the respondents are sure that their software offers accurate records, and the existing software is working effectively and at the top of its office-friendly performance. Moreover, they must prioritize updating their system. The system they are using is outdated, which could damage the staff’s trust in their ability to compete. On the other hand, innovations are rapidly expanding today.